Behavior of CFRC/Al Foam Composite Sandwich Beams under Three‐Point Bending. Issue 1 (24th July 2013) - Vcelka, Martin; Dunn, Michelle; Durandet, Yvonne; Berndt, Christopher C.; Ruan, Dong
<x xml:space="preserve">Abstract</x> The collapse mode and energy absorption of composite sandwich beams with and without defects are studied experimentally. Delamination between carbon fibre epoxy face sheets and an aluminium foam core is introduced by using a release film and measured using ultrasound before three‐point bending tests. The force and displacement are recorded from which energy absorption of the sandwich beams is calculated. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>